Measuring the Rate of Local Evaporation from the Liquid Surface under the Action of Gas Flow; Technical Physics Letters; Vol. 41, № 14 - Lyulin Y. V. Yury Vyacheslavovich; Feoktistov D. V. Dmitriy Vladimirovich; Afanasjev E. S. I. A.; Chachilo E. S. Evgeny Sergeevich; Kabov O. A. Oleg Aleksandrovich; Kuznetsov G. V. Geny Vladimirovich (2015, 2015)
Title screen